2001
DOI: 10.1101/gad.866301
|View full text |Cite
|
Sign up to set email alerts
|

A multistep damage recognition mechanism for global genomic nucleotide excision repair

Abstract: A mammalian nucleotide excision repair (NER) factor, the XPC-HR23B complex, can specifically bind to certain DNA lesions and initiate the cell-free repair reaction. Here we describe a detailed analysis of its binding specificity using various DNA substrates, each containing a single defined lesion. A highly sensitive gel mobility shift assay revealed that XPC-HR23B specifically binds a small bubble structure with or without damaged bases, whereas dual incision takes place only when damage is present in the bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
447
2
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(482 citation statements)
references
References 59 publications
22
447
2
7
Order By: Relevance
“…More detailed biochemical analyses with defined nucleic acid substrates revealed that XPC protein displays a general affinity for DNA sites that deviate from the canonical Watson-Crick geometry, including single-stranded loops, mismatched bubbles or single-stranded overhangs [35,36]. According to scanning force microscopy studies, the binding of XPC protein to DNA induces a kink of 39-49º in the nucleic acid backbone regardless of whether the substrate is damaged or not 7 [37].…”
Section: Initiation Of Ggr Activity By the Xpc Complexmentioning
confidence: 99%
“…More detailed biochemical analyses with defined nucleic acid substrates revealed that XPC protein displays a general affinity for DNA sites that deviate from the canonical Watson-Crick geometry, including single-stranded loops, mismatched bubbles or single-stranded overhangs [35,36]. According to scanning force microscopy studies, the binding of XPC protein to DNA induces a kink of 39-49º in the nucleic acid backbone regardless of whether the substrate is damaged or not 7 [37].…”
Section: Initiation Of Ggr Activity By the Xpc Complexmentioning
confidence: 99%
“…15 According to their bipartite model of NER, the NER machinery first recognizes disruptions of Watson-Crick hydrogen bonding, followed by an unspecified second verification step that ensures that a chemically modified nucleobase is indeed present. 7,8,16,48,49 This has been called an "indirect readout mechanism" by Dip et al 48 Our detailed structural analyses based on MD simulations have previously provided further insights into the nature of DNA distortions that provoke NER susceptibility. [50][51][52][53] We found that a number of other structural parameters, besides Watson-Crick hydrogen bonding, are compromised by bulky lesions, a phenomenon we termed the multipartite mechanism of lesion recognition.…”
Section: Dynamic Flexibility and Ner Damage Recognitionmentioning
confidence: 99%
“…The basic hypothesis in the field of NER is that the mammalian DNA repair apparatus recognizes structural distortions and thermodynamic destabilization in the DNA duplex caused by the lesions, followed by a verification step that detects the presence of a chemically modified nucleobase and the excision of a fragment 24-32 nucleotides long that contains the damaged base. [3][4][5][6][7][8][9][10][11] It is now established that the first and rate-determining step in NER is the recognition of the bulky lesions by the XPC/HR23B protein heterodimer complex. 12 Since the NER machinery processes a diverse array of bulky lesions with different efficiencies, the conformational features that invoke NER are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal set of proteins required to perform complete GG-NER (more than 30 polypeptides) has been defined using in vitro reconstituted systems [8,9] and specific roles have been assigned to the various factors involved. The DNA damage recognition protein complexes UV-DDB and XPC-RAD23B are required for the efficient recruitment of all of the following NER proteins to the damaged DNA [10][11][12][13]. The basal transcription factor TFIIH has an essential role in NER as two of its components, i.e.…”
Section: Global and Transcription-coupled Nucleotide Excision Repairmentioning
confidence: 99%